Nasal strips do not affect cardiorespiratory measures during recovery from anaerobic exercise - Thomas, D. Q.; Larson, B. M.; Rahija, M. R.; McCaw, S. T. (The Journal of Strength and Conditioning Research, 2001)
Nasal dilators supposedly aid recovery from exercise by reducing nasal airway resistance. Research has focused on the effectiveness of nasal dilators during exercise. The purpose of this study was to examine the effects of nasal dilators on heart rate (HR), minute ventilation (VE), and oxygen consumption (O2) during recovery from anaerobic exercise. Fourteen subjects (19-32 years) performed a modified Cunningham-Faulkner anaerobic treadmill test (1-minute walk at 2.0 miles per hour [mph], 0% grade; 1-minute jog at 5 mph, 0% grade; and sprint at 8 mph, 20% grade) under 3 randomly assigned conditions: (a) control, (b) nasal strip, and (c) placebo nasal strip. A 10-minute recovery period consisting of 5 minutes of walking (2 mph, 0% grade) and 5 minutes of passive recovery (seated) was completed. During the test and recovery periods, the participant wore a fireman's face mask to allow for simultaneous sampling of nose and mouth breathing. O2 and VE were monitored by a TEEM 100 metabolic analyzer. Each subject wore a Polar Heart Watch to monitor HR every minute during recovery. Mean time to exhaustion was 48.4 seconds (±14.9). One-way repeated-measures analyses of variance (ANOVAs) indicated no significant nasal dilator effect on 5-minute recovery HR or 10-minute recovery HR, 5-minute recovery O2 or 10-minute recovery O2, and 5-minute recovery VE or 10-minute recovery VE. Nasal strips appear to have no significant impact during recovery from anaerobic exercise.